Analysis of the Negative Externalities of Tobacco Consumption: A Fiscal Comparison of Regional Cigarette Taxes and Healthcare Costs in Tebing Tinggi - Nofi Susanti; Rani Suraya; Putra Apriadi Siregar; Abdillah Ahsan; Faiza Adinda; Nuraisyah Wulandari Panjaitan; Nurhayati Nurhayati (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
The high prevalence of smoking in Indonesia poses a substantial financial burden on the national health insurance system. At the local level, regional governments frequently encounter a fiscal dilemma between relying on revenues generated from the tobacco sector and suppressing the escalating costs of curative services driven by the adverse impacts of tobacco. This study aims to empirically examine the relationship between tobacco fiscal instruments, regional revenues, and the healthcare cost burden resulting from smoking-related diseases in Tebing Tinggi City. A quantitative approach utilizing a descriptive-comparative study design was employed to analyze secondary data spanning the 2022–2024 period. Data were obtained from the Regional Development Planning Agency of Tebing Tinggi, including realized figures for Cigarette Taxes and the Tobacco Excise Revenue Sharing Fund, as well as medical service data from Dr. H. Kumpulan Pane Regional General Hospital in Tebing Tinggi City. In 2024, the total regional revenue generated from the tobacco sector in Tebing Tinggi City reached only IDR 14.48 billion (consisting of IDR 14.19 billion from Cigarette Taxes and IDR 288.68 million from Tobacco Excise Revenue Sharing Fund. Conversely, the total medical expenditure for 11 types of smoking-related diseases swelled massively, draining the regional budget by IDR 33.05 billion in the same year, predominantly driven by catastrophic cases such as stroke and tuberculosis. There exists a hidden fiscal deficit in Tebing Tinggi City, whereby revenues from the tobacco sector fail to cover even half of the total local healthcare expenditure caused by these negative externalities. To mitigate this hidden fiscal deficit and reduce long-term curative health expenditure, a comprehensive local policy enforcing a total ban on cigarette advertising is highly recommended as a direct upstream preventive intervention. Keywords: Fiscal Deficit, Cigarette Tax, Healthcare Costs, Negative Externalities, Tobacco Excise Revenue Sharing Fund